2016
DOI: 10.1016/j.joca.2015.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Fibulin-3 fragments are prognostic biomarkers of osteoarthritis incidence in overweight and obese women

Abstract: Baseline fibulin-3 concentrations are associated with the incidence of clinical knee OA among middle-aged overweight and obese women. Therewith, they meet the criteria of a prognostic biomarker according to the BIPED biomarker classification for OA. Further validation of the fibulin-3 epitopes seems warranted in order to better distinguish subgroups of individuals at increased risk for knee OA development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 24 publications
1
21
0
1
Order By: Relevance
“…While the role of fibulin-3 in osteoarthritis is still unknown, a recent study by Henrotin et al suggests that Fib3-1 and Fib3-2 are potential diagnostic biomarkers of OA, demonstrating that serum levels of Fib3-1 and Fib3-2 in severe knee OA patients are higher than those in healthy controls [40]. Moreover, investigating middle-aged, overweight and obese women, Runhaar et al indicated that Fib3-1 correlates with the incidence of radiographic knee OA defined by American College of Rheumatology (ACR) criteria and chronic pain at 30 months of follow-up [41]. …”
Section: Biomarkers For Cartilage Bone and Synovium Metabolismmentioning
confidence: 99%
“…While the role of fibulin-3 in osteoarthritis is still unknown, a recent study by Henrotin et al suggests that Fib3-1 and Fib3-2 are potential diagnostic biomarkers of OA, demonstrating that serum levels of Fib3-1 and Fib3-2 in severe knee OA patients are higher than those in healthy controls [40]. Moreover, investigating middle-aged, overweight and obese women, Runhaar et al indicated that Fib3-1 correlates with the incidence of radiographic knee OA defined by American College of Rheumatology (ACR) criteria and chronic pain at 30 months of follow-up [41]. …”
Section: Biomarkers For Cartilage Bone and Synovium Metabolismmentioning
confidence: 99%
“…The latest research shows that miRNA has a close relationship with a variety of physiological and pathological conditions. The present study suggests that miRNA is associated with the occurrence, development and prognosis of cancer, which can be used as a molecular marker of cancer [12,13]. For example, microrna-18a is a molecular marker of prostate cancer [5]; microRNA 25, microRNA 145 and microRNA 210 are molecular markers of liver cancer.…”
Section: Introductionmentioning
confidence: 73%
“…Participants were excluded if they had any of the following: lack of motivation to lose weight, inability to speak Danish, planned anti-obesity surgery, total knee alloplasty (TKA), or receiving pharmacologic therapy for obesity. The patients were given an initial 16 week intensive diet intervention in a supervised program, inducing a clinically significant weight loss. The intensive diet intervention consisted of 8 weeks of full meal replacement (Cambridge Weight Plan TM, Northants, UK) with either 810 or 415 kcal/day followed by 8 weeks with gradual reintroduction of "normal food" in a hypo-energetic diet of 1200 kcal/day 21 .…”
Section: Studymentioning
confidence: 99%
“…We analysed the changes from week 0 using repeated measures mixed effects models, allowing for imbalanced data (i.e., no imputation for missing data beyond baseline) with maintenance group (Control, Diet, and Exercise) and week (8,16, and 68) as fixed effects including their interaction, and participant as random effects. The models were adjusted for the baseline value.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation